Dialectics of gap and the problem of systemic violence in post-Marxism - Sidorenko, Irina N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In the article, based on the analysis of philosophical concepts of K. Castoriadis, A. Badiou, S. Zizek, the essence of systemic violence is revealed as a destructive, repressive organization of social space, the result of which is the loss of the meaning of social action, alienation of a person from social and political practices. It is noted that the idea of ​​a gap is interpreted not as a source of violence, but as a means of restoring the political space and returning the politically minded and responsible actor, which makes it possible to talk about two types of violence in post-Marxism: negative (systemic) and positive (political). Within the framework of the post-Marxist philosophy, the return of political subject, the realization of the ideal of the emancipated society through social imagination, the construction of both a political subject and a new order of being by the event are considered as effective ways to limit systemic violence.